Biomechanics of head impacts associated with diagnosed concussion in female collegiate ice hockey players. Issue 10 (16th July 2015) - Wilcox, Bethany J.; Beckwith, Jonathan G.; Greenwald, Richard M.; Raukar, Neha P.; Chu, Jeffrey J.; McAllister, Thomas W.; Flashman, Laura A.; Maerlender, Arthur C.; Duhaime, Ann-Christine; Crisco, Joseph J.
Abstract Epidemiological evidence suggests that female athletes may be at a greater risk of concussion than their male counterparts. The purpose of this study was to examine the biomechanics of head impacts associated with diagnosed concussions in a cohort of female collegiate ice hockey players. Instrumented helmets were worn by 58 female ice hockey players from 2 NCAA programs over a three year period. Kinematic measures of single impacts associated with diagnosed concussion and head impact exposure on days with and without diagnosed concussion were evaluated. Nine concussions were diagnosed. Head impact exposure was greater in frequency and magnitude on days of diagnosed concussions than on days without diagnosed concussion for individual athletes. Peak linear accelerations of head impacts associated with diagnosed concussion in this study are substantially lower than those previously reported in male athletes, while peak rotational accelerations are comparable. Further research is warranted to determine the extent to which female athletes' biomechanical tolerance to concussion injuries differs from males.